The Influence of Flashcards Media in Improving Students' Speaking Skill on the First Grade of Junior High School - Ridwan Ridwan; Nurhaeni Nurhaeni (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This research aimed to know there was a significant influence of using Flashcard media in improving students' speaking skills. The location of this study was at SMPN SatapLelumpang. The research methodology was a pre-experimental design using the One-group pretest-posttest design. The population in this research were all students of class VII. This study's sample was non-probability sampling, namely saturated sampling, where the total population was 19 students. When the pre-test and post-test were completed, the researcher analysed the data using SPSS to determine the T-test sample. (2-tailed) = 0.000 and <0.05. Sig. (0.000 <0.05) indicated that flashcards media in improving students' speaking skill of seventh-grade students of SMP at SMPN Satap Lelumpang was influential and effective. It indicated an increase in students' speaking skills after using flashcards. The score for the Mean Pre-test was 59.47, while the Mean Post-test score was 65.78 where the significant value was (0,000). While students’ motivation in speaking skill towards the used of flashcards media in a mean score of 7.61  and  CTR 37%  has been able to influence the motivation to learned speaking skill in seventh grade using the flashcards media method at SMPN Satap Lelumpang. Furthermore, the analysis showed that the average score of students' motivation on the use of flashcards media in learning the speaking skill was (73.31%).